Index Iteration Theory for Brake Orbit Type Solutions and Applications (Analysis in Theory and Applications, 2021)
In this paper, we give a survey on the index iteration theory of an index theory for brake orbit type solutions and its applications in the study of brake orbit problems including the Seifert conjecture and the minimal period solution problems in brake orbit cases.